Evaluation of Carbon Sequestration Benefits of Ecological Restoration in Open Pit Mines —— A Case Study of Tongluo Mountain Mine - Li Manyi; Ma Lei; Wang Chen; Mao Zheng; Xu Mingze; Zhu Dongxue; Li Cheng (E3S Web of Conferences)
The study takes Tongluo Mountain Mine in Chongqing as the test site, the plant and soil carbon sinks of different ecological restoration land use types were measured and the main influencing factors were analysed by means of plant investigation, plant biomass measurements, soil physicochemical property tests and model simulations. The main conclusions of the study are as follows:(1) The carbon sink per unit area of plant (4.65 kg C/m2), the carbon sink per unit area of soil (4.36 kg C/m2), the total carbon sink (574.39 t C), the carbon sink of vegetation (36.77 t C), and the carbon sink of soil (538.79 t C) are higher, but the carbon sink per unit area of vegetation is lower (0.29 kg C/m2). The carbon sink of mine ecological restoration mainly comes from soil carbon sink, and the carbon sink per unit area of soil (4 kg/m2) is 8 times higher than that of vegetation (0.5 kg/m2).;(2) The main influencing factors of vegetation carbon sink are vegetation growth, and the main influencing factors of soil carbon sink are soil organic matter and soil fertility;(3) In the ecological restoration of open-pit mines, more local tree species such as yellow camphor, cinnamomum camphor and acanthopanax were planted, and measures such as increasing soil thickness and clay content in soil were taken to improve the regional soil ecological environment.